Modeling and simulation of radial combustion propagation of Fe2O3/Al thermite systems - Brito, Paulo (2011)
In previous works, a one-dimensional model was built to simulate the non-steady radial combustion propagation on thin disk shaped samples of Fe2O3/Aluminum thermite mixtures and was successfully tested. Now, the purpose is to extend the referred model to the more sensible two-dimensional features of the samples, maintaining the main characteristics of the previous model: zero order kinetics, conductive/radiative heat transfer, assumption of phase transitions, temperature and composition variation of all system properties during propagation. Therefore, an adaptive numerical algorithm that conjugates a Method of Lines (MOL) strategy based on finite differences space discretizations, with a collocation scheme based on increasing level dyadic grids is applied for the solution of the problem. The model validation implies the comparison of numerical results with available experimental data obtained in similar conditions. Thus, the particular integration method proves to cope satisfactorily with the steep travelling thermal wave in 1D and 2D spatial domain supports, either for trivial uniform mixing conditions, as in complex examples developed to feature more sophisticated circumstances, such as non-homogeneous reactant mixing, and selective pseudo-random directional flame extinction, which realistically replicate the observed experimental phenomena.